IMPLEMENTASI KEAMANAN VIRTUAL PRIVA TE NETWORK - Haryono . (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2008)
Intranet is an adoption of internet technology connecting local computer network to all computer networks in the world. Intranet is object to the attacks of computer system security. It implement a Virtual Private Network (VPN). A technique that can solve the broblem is by using Firewall. I It’s technology consist of three basic architectures: dual ported host, screened host, and screened subnet. By using one of thejirewall architectures, each computer system in the intranet computer network is secure from the attack. It will reduce the risk of Information System from Fault Accident.